ANALISIS PERSEPSI MASYARAKAT TENTANG PELAYANAN PADA OBJEK WISATA SI BEA-BEA KABUPATEN SAMOSIR - Nadya Pelmawati Situmorang; Marlan Hutahaean; Vera Pasaribu (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
This study aims to analyze public perceptions of services at the Sibea-Bea tourist attraction in Samosir Regency and identify influencing factors. Sibea-Bea is a rapidly developing, leading tourist destination in the Lake Toba area, with its main attractions being natural panoramas and religious tourism. However, over time, the services provided to tourists have been deemed suboptimal, influencing public perception. The research results show that public perception of services at the Sibea-Bea tourist attraction is generally considered quite good. This is evidenced by the SERVQUAL service quality dimensions, which include physical appearance, reliability, responsiveness, assurance, and empathy. The empathy and assurance dimensions received the highest ratings due to the friendly attitude of the community and the sense of security felt by tourists. However, the physical appearance dimension still faces shortcomings, particularly in public facilities such as toilets, trash cans, and rest areas. Furthermore, limited staffing also hampers optimal service delivery.